MODIFIKASI DAN PENINGKATAN KINERJA UNIT SARPALAM KAPASITAS 5 LITER/DETIK, DI DESA SOMBA, KECAMATAN SENDANA, KABUPATEN MAJENE, SULAWESI SELATAN - Herlambang, Arie (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2003)
Slow Sand Filter Technology is very common water technology that is used inmany villages in Indonesia, because very simple, low operating and lowinvestment cost. Sarpalam is the acronym of Saringan Pasir Lambat (Slow SandFilter). For optimal process, the system should meet with the standard design forSlow Sand filter. Somba is one village that is situated in Northern Part of SouthSulawesi. In that village there is a Slow Sand Filter with 5 l/s capacity to servearound 5.000 people. The problem is the quality of water is very low, turbid andsmell. The source of water come from the hill, in the eastern part (around 3 kmup hill). After investigation founded that, the system is not meet with standardSlow Sand filter and need modification for increasing the quality of product water. There are some constrain in the modification of the system, namely : existing construction, lack of space in the hill, stability of land, and quality of product water.